A Proposed Unified Standard IoT-Based Architecture Based on 7-Layers Framework (Case Applied: Car Accident System) - Saleh Hussien Al-awami; Mousa Faraj Al-najar (Journal of Pure & Applied Sciences, 2022)
Internet of Things (IoT) is one of the famous applications of internet commuting and of cloud computing, and it is a widely used applications by organizations or by individuals, i.e., smart city, smart home, etc. There are many different IoT platforms that have been developed and used by IoT cloud providers to provide services to their subscribers. These different platforms lead to difficulty understand of each platform by developers. So, the need of IoT standard system is highly required to mitigate the diversity of building IoT-based system using different software layers. In this paper, a unified IoT-based architecture has been proposed based on 7-layers framework to be as a de facto standard to the most of IoT-based applications. Moreover, the proposed architecture has been applied using the car accident system which is a known application of IoT based application using CubCarbon Wireless Senser Networks (WSN) simulator. The proposed architecture shows the consistency between its 7-layers and promising to be as a considered unified IoT architecture.